Social change, preserving what is valuable - Stănescu, Nina; Tasențe, Tănase (Technium Social Sciences Journal, 2021)
Social relationships are generally defined as that type of interconnection between two, three or more social actors acting together, thinking together, feeling together, waiting or asking for an answer from one another, within life manifestations or common, palpable, sustainable and meaningful activities. The foundation of social relationships (and their framework) is, therefore, represented by the manifestation of life that includes at least two individuals. When this life manifestation takes the form of the meaning of life, the foundation of a social action and, thus, the manifestation of a social relationship, is created. When the manifestation of life takes the form of a professional activity, we say that it has a professional meaning. The meaning of life is expressed in connection to the profession and, cumulatively, as a vocation”